ICES (Intraoperative Stereotactic Computed Tomography-Guided Endoscopic Surgery) for Brain Hemorrhage: A Multicenter Randomized Controlled Trial. Issue 11 (November 2016) - Vespa, Paul; Hanley, Daniel; Betz, Joshua; Hoffer, Alan; Engh, Johnathan; Carter, Robert; Nakaji, Peter; Ogilvy, Chris; Jallo, Jack; Selman, Warren; Bistran-Hall, Amanda; Lane, Karen; et al.
Abstract : Background and Purpose—: Intracerebral hemorrhage (ICH) is a devastating disease without a proven therapy to improve long-term outcome. Considerable controversy about the role of surgery remains. Minimally invasive endoscopic surgery for ICH offers the potential of improved neurological outcome. Methods—: We tested the hypothesis that intraoperative computerized tomographic image–guided endoscopic surgery is safe and effectively removes the majority of the hematoma rapidly. A prospective randomized controlled study was performed on 20 subjects (14 surgical and 4 medical) with primary ICH of >20 mL volume within 48 hours of ICH onset. We prospectively used a contemporaneous medical control cohort (n=36) from the MISTIE trial (Minimally Invasive Surgery and r-tPA for ICH Evacuation). We evaluated surgical safety and neurological outcomes at 6 months and 1 year. Results—: The intraoperative computerized tomographic image–guided endoscopic surgery procedure resulted in immediate reduction of hemorrhagic volume by 68±21.6% (interquartile range 59–84.5) within 29 hours of hemorrhage onset. Surgery was successfully completed in all cases, with a mean operative time of 1.9 hours (interquartile range 1.5–2.2 hours). One surgically related bleed occurred peri-operatively, but no patient met surgical safety stopping threshold end points for intraoperative hemorrhage, infection, or death. The surgical intervention group had a greater percentage of patients with good neurological outcome (modified Rankin scale score 0–3) at 180 and 365 days as compared with medical control subjects (42.9% versus 23.7%; P =0.19). Conclusions—: Early computerized tomographic image–guided endoscopic surgery is a safe and effective method to remove acute intracerebral hematomas, with a potential to enhance neurological recovery. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00224770. Abstract : Supplemental Digital Content is available in the text.